Comparison of the bioavailability of benzo[a]pyrene (B[a]P) in a B[a]P-contaminated soil using the different addition approaches - Ye, Xinxin; Ma, Jingjing; Wei, Junling; Sun, Kai; Xiong, Qizhong (Scientific reports, 2019)
Determination of the bioavailability of the hydrophobic organic contaminant benzo[a]pyrene (B[a]P) is extremely important for assessing its environmental risk. The effect of addition manner of B[a]P on the bioavailability and toxicity of B[a]P in soil remains unclear. In this study, soil samples, spiked with B[a]P by one-time or multiple-time additions, were tested to investigate the available fraction of B[a]P in soils, the uptake of B[a]P by red wiggler worms ( Eisenia fetida ), as well as superoxide dismutase (SOD) and peroxidase (POD) activities in earthworm coelomocytes at different periods. Results showed that the available fraction of B[a]P in soils and the amount of B[a]P assimilated by earthworms declined sharply from 1 d to 28 d during the incubation period and then decreased slowly from 28 to 56 d in both the one-time and the multiple-time addition tests. The available fraction of B[a]P in soils and its uptake by earthworms were significantly lower in multiple-time addition samples than those in one-time addition samples, a finding which was consistent with the SOD and POD activities in earthworms during the whole 56-d incubation period. These variations in the characteristics of the two addition treatments may be due to the differences in the way the B[a]P aged in the soil. These results indicated that the addition method was an important factor influencing the bioavailability of organic contaminants in soils.